The Madonna and the Cuckoo: an exploration in European symbolic conceptions - Vaz da Silva, F. (2007)
The main hypothesis underlying this paper is that tiny faults in the seamless conceptual order of things may reveal unsuspected realms of meaning. The following discussion makes a case for this by examining a minute ethnographic problem at a Marian sanctuary in northern Portugal. But seeming pointless trivia may only yield insight into worldview, so goes the argument, on the condition that the analysis of data unfolds beyond both the conscious formulations of informants and the immediate ethnographical context. In other words, to get beyond the superficial aspect of things requires a comparative procedure. Hence, this piece is an experiment in the reconstitution of plural, interlocking contexts for the purpose of symbolic analysis. From a local question regarding the identity of a bird on statues depicting the Holy Family at the Portuguese sanctuary, the inquiry will unfold through folklore, ethnography, Christian art, and the Scriptures to evoke the mental landscapes that could reveal the enigmatic bird and make sense of it. As a solution gradually emerges, the newly found bird will, in turn, bring to light some basic traits of a metaphysical theory of reproduction that has long been perennial in Western cultures and, in fact, beyond.